Essays on globe energy consumption and economic growth nexus - Marques, Luís Miguel Soares Santos (2018)
The way that economic growth and energy consumption interact with each other has been a rising interest in the last few decades. The continuous globe economic growth and the shift in large energy demand to emerging economics such as India and China raise new challenges requiring study. Regarding this, the literature is scarce and the study of energy-growth nexus at higher macroeconomic levels has been overlooked. The worldwide changes occurring in energy markets are expected to raise interest in globe nexus. In order to evaluate the interactions between globe economic growth and energy consumption, bivariate and multivariate models were developed. The aim of this research in not only to examine both short- and long-run nexus behaviours, but also to identify how the energy policies that some countries can follow, or how the development of globalization can have an impact on a globe scale. Following this path, different variables were introduced as explanatory of globe economic growth and energy consumption. By developing four essays, the thesis seeks to raise awareness of the importance of understanding the impact of economic policy decisions at the globe level. The first two essays focus on studying the energy-growth nexus at the globe level and by dividing the globe into four regions, without interference from any other variables. The third and fourth essays introduce the concept of study of the globe augmented energy-growth nexus. Additionally, in the third essay, China’s economic growth and energy consumption were introduced as possible explanatory variables of economic growth and energy consumption through different globe regions. The fourth essay, examines the impact of different globalization dimensions on globe energy-growth nexus. The followed econometric approaches considered the data requirements as well as the predictable presence of structural breaks. Moreover, the aim to examine both the short- and the long-run relationships influenced the methodology choice. For those reasons, autoregressive models such as Autoregressive Distributed Model (ARDL), Vector Autoregression (VAR) or Vector Error Correction Model were developed by using time series and panel data. The results reveal a bidirectional relationship between globe economic growth and energy consumption. Moreover, the existence of heterogeneous relationships in different globe regions is proven to mostly not come from the use of different methodologies. Overall, the results support a path of diversification, not only on the used primary energy components, but also on economic outputs sources. It has also been proven that there are countries, such as China, that can influence the globe nexus. Regarding other factors influencing the globe nexus, it was observed that there are different globalization components impacting on globe economic growth and energy consumption.